INCOME-SPECIFIC INFLATION RATES AND THE EFFECTS OF MONETARY POLICY: THE CASE OF NORTH MACEDONIA - Jovanovic, Biljana; Josimovski, Marko (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
In this paper, we investigate the effects of monetary policy concerning the inflation rates specific for each income group of households. We find that the prices specific for high-income households are generally more rigid and less volatile compared to the prices specific for middle and lower-income households. This means that monetary policy can differently affect the different inflation rates specific for each of the income groups. By using a Factor-Augmented VAR (FAVAR) model, we show that a monetary policy shock affects high-income households less compared to middle and lower-income households, although the differences between the separate income groups are generally small. Then, by using a small scale gap model, we find that the prices of low-income households are the most sensitive to a monetary policy shock, while the prices of the top-income households are the least sensitive to the shock, which is in line with our empirical findings.
Keywords: Inflation; monetary policy; distributional effects